Tuturan Langsung dan Tidak Langsung antara Penjual dan Pembeli di Pasar Tradisional Semarang - Sri Puji Astuti (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2019)
The purpose of this research is to describe speech acts that occur between seller and buyer in traditional market. Data was obtained using the method of observation and recording techniques. After the data were collected, the data were analyzed by using pragmatic theory, especially speech acts. Based on the results of the research were found the types of speech acts used between sellers and buyers in traditional markets, namely literal direct speech acts, non-literal direct speech acts, literal indirect speech acts, and non-literal indirect speech acts. Literal direct speech acts were used by sellers and buyers because the seller's and the buyer's l could be straightforward and clear, when the seller was angry with the buyer and the seller insinuated the other sellers.